Some Remarks on Latin Legal Terminology in the Works of Adam Mickiewicz - Szczygielski, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Adam Mickiewicz is considered to be the most outstanding Polish Romantic poet, as well as one of the most excellent poets of Europe. Interestingly, Mickiewicz used in his works expert Latin legal terminology relating to the issues of social structure, political organization of the Roman state and Roman law. His knowledge on this subject came mainly from the works of ancient writers with which he became familiar while studying at the Vilnius University. Mickiewicz also read publications that dealt extensively with the history of ancient Rome by authors such as Edward Gibbon, Barthold Georg Niebuhr, Jules Michelet, and Joachim Lelewel.